MULTI-CRITERIA ANALYSIS OF DEMOGRAPHIC DEVELOPMENT LEVEL OF THE REGIONS IN SERBIA - Petrović, Jelena; Radukić, Snežana; Radović, Milica (Poslovna ekonomija, 2018)
Regional differences are one of the most important forms of expression of uneven economic development. The unevenness of the level of development in the regions in the Republic of Serbia is one of the most complex development problems. The current economic policy has caused that the gap between rich and poor regions is increasing in Serbia. Different demographic development of the regions is consequences of differences of economic development. In this paper, the authors analyze the quantitative and qualitative population`s characteristics. Attention is given to the implementation of VIKOR methods in order to rank the regions of Serbia according to the level of demographic development. Ranking regions by multiple criteria simultaneously, contributes to the determination of the real situation in terms of regional differences. The authors demonstrate that the multi-criteria analysis could be applied to determine the demographic disparities between the levels of development of the regions. The criteria and their importance could be changed depending on the consideration of demographic, economic and social development. Also, other methods of multi-criteria analysis in the evaluation of the demographic development of the region or state is applied.